Variation of the power as a function of module temperature for different thin film modules. - Cañete-Torralvo, Cristina; Moreno-Sáez, Rafael Jesús; Carretero-Rubio, Jesús Eduardo; Piliougine Rocha, Michel; Sidrach-de-Cardona-Ortin, Mariano (WIP Munich, 2012)
The aim of this study is to determine the evolution of the power of photovoltaic modules of different technologies and their temperature dependence through one year. For this purpose, photovoltaic modules of CdTe, a-Si, a-Si/c-Si and pc-Si have been installed under outdoor conditions on the roof of the photovoltaic laboratory at the University of Málaga, Spain. The obtained results show a variability of the peak power that is a function of the variation of the incident irradiance spectrum. However, this influence on the measured peak power is different for each technology. Thin film modules have higher peak power variability throughout the year than conventional modules. The amorphous silicon module presents the greatest annual variability, reaching 7.4% its nominal power. The polycrystalline silicon module is the most stable with an annual variation of 1.5% of its nominal power. No irreversible damage has appreciated in the tested modules during this period. We have determined the power thermal coefficient for clear-sky days throughout the year. The results show that the variation of this coefficient depends on the temperature of the module.
Keywords: Colectores solares; PV Module; Reliability; Thin Film